Constraint Analysis of Farming on House Terraces - Binsa, B; Sreedaya, G.S Gopinathan (Journal of Extension Education, 2019)
A study was carried out to identify the constraints in farming on house terraces and in the distribution of grow bags in Thiruvananthapuram Corporation in Kerala. The study was conducted in seven wards of Thiruvananthapuram Corporation namely Poojappura, Pettah, Manacaud, Kumarapuram, Karamana, Industrial Estate and Enchakkal. One hundred and five members of urban households involved in farming on house terrace, fifteen extension officials and thirty office bearers of selected residents’ associations of the selected wards were the respondents of the study. Regarding the constraints perceived by the respondents on farming on house terrace, ‘crop loss due to pests and diseases attack’ was perceived as the major constraint and ‘low quality grow bags and potting mixture issued by the private agencies’ was the major constraint in the distribution and usage of grow bags as perceived by the respondents and office bearers of residents associations. ‘Lack of timely availability of funds’ was the major constraint in the scheme on farming on house terrace and growbag distribution as perceived by the extension officials.